ETHNOMATHEMATICAL E-COMIC: ENHANCING STUDENTS’ SELF-EFFICACY AND DIVERGENT THINKING - Budi Wahyu Pertiwi; Gunawan Gunawan (JURNAL EDUSCIENCE, 2026)
Purpose—Mathematics learning often remains abstract and disconnected from students’ cultural experiences, which limits creativity and engagement. This study addresses that gap by integrating ethnomathematical content into digital comic media to strengthen students’ self-efficacy and divergent thinking skills.Methodology—A quasi-experimental design using a pretest–posttest control group was employed. The population consisted of seventh-grade junior high school students, and the sample included two classes (N = 52) selected through cluster random sampling. Each class comprised 26 students, with one designated as the experimental group and the other as the control group. The experimental group received instruction using ethnomathematics-based e-comics, while the control group used PowerPoint. Instruments included a self-efficacy questionnaire and a divergent thinking test. Data were analyzed using descriptive statistics and a one-way MANCOVA.Findings—The MANCOVA results showed a significant effect of ethnomathematical e-comic media on both self-efficacy and divergent thinking (Wilks’ Lambda = 0.152, F (2,47) = 131.381, p < 0.05, η² = 0.848). Self-efficacy indicators such as persistence and task commitment improved significantly, while divergent thinking indicators, fluency and flexibility, also increased markedly between pretest and posttest.Contribution—Theoretically, this study contributes to mathematics education by integrating ethnomathematics and digital learning media to support creativity-related skills. Practically, it provides teachers with innovative tools to make geometry learning more engaging and culturally relevant for students in the digital era.